Russian Federation : 2019 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Russian Federation discusses that growth is projected at 1.2 percent in 2019, reflecting a weak first quarter estimate, lower oil prices and the impact of the higher value-added tax rate on private consumption. At the same time, gross domestic product growth should be supported by an increase in public sector spending in the context of the national projects announced in 2018. Inflation has begun to fall and is expected to return to the 4 percent target by early 2020. The medium-term growth outlook remains modest. Public infrastructure spending under the national projects together with increase labor supply due to pension reform could have a positive effect on the growth rate of potential output. However, absent deeper structural reforms, long-run growth is projected to settle around 1.8 percent. It is recommended that it is imperative to enhance competition by facilitating entry/exit and reforming public procurement.